Transient Ca2+ depletion of the sarcoplasmic reticulum at the onset of reperfusion - Valverde, Carlos Alfredo (2010)
AimsMyocardial stunning is a contractile dysfunction that occurs after a brief ischaemic insult. Substantial evidence supports that this dysfunction is triggered by Ca2+ overload during reperfusion. The aim of the present manuscript is to define the origin of this Ca2+ increase in the intact heart.Methods and resultsTo address this issue, Langendorff-perfused mouse hearts positioned on a pulsed local field fluorescence microscope and loaded with fluorescent dyes Rhod-2, Mag-fluo-4, and Di-8-ANEPPS, to assess cytosolic Ca2+, sarcoplasmic reticulum (SR) Ca2+, and transmembrane action potentials (AP), respectively, in the epicardial layer of the hearts, were submitted to 12 min of global ischaemia followed by reperfusion. Ischaemia increased cytosolic Ca2+ in association with a decrease in intracellular Ca2+ transients and a depression of Ca2+ transient kinetics, i.e. the rise time and decay time constant of Ca2+ transients were significantly prolonged. Reperfusion produced a transient increase in cytosolic Ca2+ (Ca2+ bump), which was temporally associated with a decrease in SR-Ca2+ content, as a mirror-like image. Caffeine pulses (20 mM) confirmed that SR-Ca2+ content was greatly diminished at the onset of reflow. The SR-Ca2+ decrease was associated with a decrease in Ca2+ transient amplitude and a shortening of AP duration mainly due to a decrease in phase 2.ConclusionTo the best of our knowledge, this is the first study in which SR-Ca2+ transients are recorded in the intact heart, revealing a previously unknown participation of SR on cytosolic Ca2+ overload upon reperfusion in the intact beating heart. Additionally, the associated shortening of phase 2 of the AP may provide a clue to explain early reperfusion arrhythmias.